2019
DOI: 10.1097/rlu.0000000000002810
|View full text |Cite
|
Sign up to set email alerts
|

A Machine-Learning Approach Using PET-Based Radiomics to Predict the Histological Subtypes of Lung Cancer

Abstract: Purpose We sought to distinguish lung adenocarcinoma (ADC) from squamous cell carcinoma using a machine-learning algorithm with PET-based radiomic features. Methods A total of 396 patients with 210 ADCs and 186 squamous cell carcinomas who underwent FDG PET/CT prior to treatment were retrospectively analyzed. Four clinical features (age, sex, tumor size, and smoking status) and 40 radiomic features were investigated in terms of lung ADC subtype predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 15 publications
5
87
0
1
Order By: Relevance
“…This study also explored whether the prediction performance based on radiomics could be further improved by combining with clinical factors and tumor marker levels. The Combined Model established in the present study not only significantly improved the prediction efficiency for subtype compared to these factors alone in both the training and validation sets (AUCs = 0.932 (training set), 0.901 (validation set), respectively) but also had higher performance than previous researches [14][15][16][17]. This discrepancy may be related to the complete and standard preoperative baseline data and postoperative pathological reports from a single center, as well as the appropriate algorithm [37].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This study also explored whether the prediction performance based on radiomics could be further improved by combining with clinical factors and tumor marker levels. The Combined Model established in the present study not only significantly improved the prediction efficiency for subtype compared to these factors alone in both the training and validation sets (AUCs = 0.932 (training set), 0.901 (validation set), respectively) but also had higher performance than previous researches [14][15][16][17]. This discrepancy may be related to the complete and standard preoperative baseline data and postoperative pathological reports from a single center, as well as the appropriate algorithm [37].…”
Section: Discussionmentioning
confidence: 48%
“…18 F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT)-based radiomics have been shown to have potential in differentiating ADC from SCC [14,15]. Further studies have revealed that the discrimination performance could be further improved by combining with clinical features, like sex and smoking history (area under curve (AUC) = 0.859), which are higher than that of radiomic alone [16,17]. However, only PET radiomic parameters were extracted and analyzed in the above studies.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the non-imaging data in multimodal fusion work was limited, particularly in the context of available featurerich and time-series data in the EHR. Instead, most studies focused primarily on basic demographic information such as age and gender 25,27,39 , a limited range of categorical clinical history such as hypertension or smoking status 32,34 or disease-specific clinical features known to be strongly associated with the disease of interest such as APOE4 for Alzheimer's 25,28,33,36 or PSA blood test for prediction of prostate cancer 40 . While selecting features known to be associated with disease is meaningful, future work may further benefit from utilizing large volumes of feature-rich data, as seen in fields outside medicine such as autonomous driving 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Out of these five studies, two applied feature selection strategies to reduce the feature dimension and improve predictive performance. The employed feature selection strategies included a rank-based method using Gini coefficients 32 , a filter-based method based on mutual information of the features 35 , and a genetic-algorithm based method 35 . Seven of the early fusion studies compared the performance of their fusion models against single modality models ( Table 1).…”
Section: Early Fusionmentioning
confidence: 99%
“…Ten trials were designed to diagnose lung cancer. In terms of the imaging diagnosis of lung cancer, it was reported that machine learning could predict the histological type of lung cancer through the imaging characteristics of PET/CT (18).…”
Section: Discussionmentioning
confidence: 99%